Analysis of maternal care and nurse care in Primary Health Care for a child with microcephaly (Research, Society and Development, 2022)
The objective of this research was to verify how the nurse-mother relationship/bond of children with microcephaly occurs, in addition to knowing the nursing care in the care provided to the mother-child binomial with congenital alterations, identifying the health actions developed for the child with microcephaly. This is a descriptive study with a qualitative approach. The study was carried out with nurses from the Family Health Strategies (FHS) of a municipality in the Triângulo Mineiro region. For data collection a semi-structured interview was used and the final material was submitted to Content Analysis. As a result, we found that the analysis of care generates complicating points such as the lack of specialization that helps in the improvement of professionals and the facilitating points are in the family's discernment process to understand the care/assistance to be provided. broken. The present study concluded with important reflections about the actions, knowledge and various facilitating/complicating points on the analysis of care for mothers of children with microcephaly and how nurses deal with the need to promote family adherence.